PROFESIONALISME GURU PENDIDIKAN AGAMA ISLAM DI ERA TEKNOLOGI INFORMASI DAN KOMUNIKASI - Kartilawati Kartilawati; Mawaddatan Warohmah (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2014)
The globalization era, which is started from the information and communication technology, requires the professionalism of the workers including the teacher. Professionals are workers who have skill, ability, and realize if the profession has an responsibility in work. Therefore, the teacher should improve the professionalism. The information technology progress will be useless if the teachers feel skeptic for this progress. The teacher should have an attitude whether he/she accept or reject to information technology. Furthermore, wether the teacher accepts the role paradigm which has been shifted because of information technology progress or not.The utilization of information technology to provide teacher professionalism could be implemented by two ways, they are: 1) the use of computer programs such as Microsoft Word, Excel, and Power Point program to analyze the data and teaching media; and 2)the use of internet as learning source, communication tool, and some information source through email, mailing list, facebook, and blog.